Effect of Aromatherapy on Nausea and Vomiting of Cancer Patients Undergoing Chemotherapy: A Randomized Controlled Trial - Abd Al-Sada, karrar Hassan Abd Al-Sada; Abed, Rajaa Ibrahim (Iraqi National Journal of Nursing Specialties, 2024)
Objective(s): The aim of this study is to determine the effectiveness of aromatherapy in reducing nausea and vomiting in adult patients receiving chemotherapy. Methods: A randomized controlled trial was conducted on 66 patients with cancer undergoing chemotherapy at the Oncology Centre in Al-Kut City, Iraq, from November 7th, 2023, to June 13th, 2024. Patients were selected conveniently and randomly based on the inclusion criteria, and they were randomly assigned into two groups: the inhalation aromatherapy group and the control group. The first group inhaled peppermint oil for 20 minutes, while the control group did not receive any intervention and underwent only routine treatment. The Rhodes Index Scale was used to assess nausea and vomiting. Used SPSS version 26 to analyze the data, applying both descriptive and inferential analysis, and a one-way ANOVA test was used to determine the statistically significant difference between the two trial groups. Results: The findings revealed that there was a significant difference in the severity of nausea and vomiting in the aromatherapy groups compared to the control group, according to the mean of the aromatherapy group, which was 12.63, with a P value of 0.001. Conclusion: The Aromatherapy was found to be effective in reducing nausea and vomiting levels when compared to the control group. Therefore, inhalation of aromatherapy is recommended as an effective non pharmacological intervention to reduce nausea and vomiting related to chemotherapy. Recommendations: The study recommends healthcare professionals, particularly nurses to utilize nonpharmacological techniques such as aromatherapy that have been validated as effective more often for alleviating nausea and vomiting caused by chemotherapy.